1975
DOI: 10.33584/jnzg.1975.37.1445
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Establishment of Ryegrass Seedlings in Soldier Fly-Infested Land

Abstract: Soldier fly, Inopus rubriceps (Macquart), larvae suck nutrients from the roots of ryegrass, 'reducing root growth, tiller and foliage production, and probably plant survival. Accurate placement of insecticide with the seed killed larvae, and en'hanced establishment of the seedlings. The use of minimum cultivation, paraquat, and fertilizer sown with the seed, all made larvae move on to the rows of new seedlings thereby improving the efficiency of the insecticide and establishment of the seedlings. This was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Consequently, there are many reports of establishment failures attributed to pests and improved seedling establishment from insecticide, molluscicide and nematicide use when direct drilling pastures. Dixon & Davison (1975), Rowe & MacKay (1975), Dixon (1977) and Davison et al (1979) establish that larvae oflnopus rubriceps Macquart (Diptera: Stratiomyzidae) move onto rows of seedlings and concluded that this movement enhances the effectiveness of insecticides placed with the seed. The use of herbicide to remove existing plant cover before drilling resulted in improved larval control as the insects were forced to feed on the toxic seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there are many reports of establishment failures attributed to pests and improved seedling establishment from insecticide, molluscicide and nematicide use when direct drilling pastures. Dixon & Davison (1975), Rowe & MacKay (1975), Dixon (1977) and Davison et al (1979) establish that larvae oflnopus rubriceps Macquart (Diptera: Stratiomyzidae) move onto rows of seedlings and concluded that this movement enhances the effectiveness of insecticides placed with the seed. The use of herbicide to remove existing plant cover before drilling resulted in improved larval control as the insects were forced to feed on the toxic seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate placement of the insecticide with the seed is highly desirable in order that seedling roots have immediate access to the material. It has been shown that inclusion of an insecticide at time of sowing controls soldier fly larvae, resulting in improved seedling establishment through development of vigorous root and shoot systems (Dixon & Davison 1976).…”
Section: Introductionmentioning
confidence: 99%